A Study on Relationship between Organizational Justice and Turnover Intentions in Malaysian Manufacturing Industries - Azami, N. A.; Ungku Ahmad, U. N.; Choi, S. L. (Journal of Advanced Research in Business and Management Studies, 2020)
This paper provides insight into the relationship between organizational justice and turnover intentions. Employees own attitudes and behaviors at work will be influenced by the organization’s behavior, decision and actions. If the organization failing to manage all the function and activities properly, possibility of employee intend to leave the organization is high. Therefore, this paper discusses the concepts and previous studies that relate to the above issues.